Inclusive Education and Social Justice: A Sociological Literature Review of Equity and Access in Learning Environments - Hikmat (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This article explores the intersection of inclusive education and social justice through a sociological lens, focusing on issues of equity and access in learning environments. Inclusive education has emerged as a critical framework for addressing systemic inequalities that marginalize diverse learners across different contexts. By employing a literature review method, this study synthesizes theoretical perspectives and empirical findings to highlight how inclusive practices contribute to broader goals of social justice. The review draws on scholarly works from sociology, education, and policy studies to provide a comprehensive understanding of inclusive education as both a pedagogical and social project. Findings indicate that while inclusive education policies have been widely adopted, persistent disparities remain in the implementation of equitable learning opportunities. The analysis reveals that structural barriers, cultural attitudes, and resource inequalities continue to undermine the realization of genuine inclusivity. Furthermore, the literature demonstrates that inclusion cannot be separated from broader struggles for equity in society, as schools often reflect and reproduce social hierarchies. This review underscores the need for more critical engagement with power relations and systemic reforms in advancing inclusive education. The paper also emphasizes the importance of linking inclusive practices to community participation, teacher training, and supportive policies. This article contributes to the academic discourse by framing inclusive education as a sociological issue central to achieving social justice in contemporary education systems.